2014
DOI: 10.3892/mmr.2014.2348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vascular grafts based on polyvinyl alcohol cryogels

Abstract: The present study designed and developed blood vessel substitutes (BVSs) composed of polyvinyl alcohol (PVA) cryogels. The in vitro results demonstrated that the coating of the polymer with lyophilized decellularized vascular matrix (DVM) greatly enhanced the adhesion of human umbilical vein endothelial cells (HUVECs). However, when PVA̸DVM BVSs were implanted into the abdominal aorta of Sprague‑Dawley rats, DVM was identified as a highly thrombogenic surface resulting in the mortality of all animals 3‑4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, the decellularization process can also damage the ECM ( Simon et al, 2003 ), thus negatively affecting the integrity, and mechanical properties of the graft. On the other hand, lyophilization is a physical technique that reduces calcification, and provides a stable graft ( Conconi et al, 2014 ; Bai et al, 2019 ). Nevertheless, mechanical properties, such as suture strength, are not sufficient for clinical use ( Reinhardt et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the decellularization process can also damage the ECM ( Simon et al, 2003 ), thus negatively affecting the integrity, and mechanical properties of the graft. On the other hand, lyophilization is a physical technique that reduces calcification, and provides a stable graft ( Conconi et al, 2014 ; Bai et al, 2019 ). Nevertheless, mechanical properties, such as suture strength, are not sufficient for clinical use ( Reinhardt et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…1821 However, there has been an existing interest of using biopolymeric cryogels in biological and medical applications. 2226…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] However, there has been an existing interest of using biopolymeric cryogels in biological and medical applications. [22][23][24][25][26] There were several studies reported about the use of gelatin as the main component of any blend cryogels because gelatin is cheap, is easy to manipulate, and it is easy to get a proper mechanical strength comparable to Col. But unfortunately, its biological inductive effect is almost insignificant when comparing with Col. On the other hand, using Col alone for the construction can also be troublesome because it is more sensitive to gelation and manipulation which will lead to weak gel structure and a poor mechanical property.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymers have been used to obtain TEBVs: poly(dimethylsiloxane), poly‐ ε ‐caprolactone (PCL), poly(methyl methacrylate), poly‐ l ‐lactic acid (PLLA), polyglycolic acid, poly(glycerol sebacate), and polyvinyl alcohol . Several studies have shown that the behavior of vascular cells (fibroblasts, endothelial, and muscle cells) depends on the topography of biomaterial: presence of fibers or pores, pore size of the fibers, spacing between these elements, roughness, orientation of the fibers, and microscale or nanoscale .…”
Section: Introductionmentioning
confidence: 99%